The Relationship Between Emotional Intelligence and Diabetes Management: A Systematic Review - Pérez-Fernández, Aida; Fernández-Berrocal, Pablo; Gutiérrez-Cobo, María José (Frontiers in Psychology, 2021)
Diabetes has been associated with affective disorders which complicate the management of the disease. Emotional intelligence (EI), or the ability to perceive, facilitate, understand, and regulate emotions, has shown to be a protective factor of emotional disorders in general population. The main objective of this study was to systematically review the role of the EI construct in Type 1 and Type 2 diabetics and to observe how EI is related to biological and psychological variables. Comprehensive searches were conducted in PubMed, Scopus, PsycInfo, and Cochrane without time limitations, for studies examining the link between diabetes and EI. A total of 12 eligible studies were selected according to the inclusion criteria. We divided the results into four sections: (1) EI and hemoglobin glycosylated (HbA1c), (2) EI training effects, (3) differences in EI between persons with diabetes and without diabetes, and (4) EI and psychological adjustment and well-being. The results showed negative correlations between EI and HbA1c, positive effects of EI training on quality of life, anxiety, and glycemic control, no differences in EI between people with diabetes and healthy individuals, and, finally, negative correlations between EI and different psychological variables such as diabetes-related anxiety and distress, and positive correlations with quality of life, well-being, and marital satisfaction. This systematic review offers a starting point for a theoretical and practical understanding of the role played by EI in the management of diabetes and reveals that EI is a promising protective factor for biological and psychological variables in this population.